Hypocrisy : the tales and realities of drug detainees in China - Cheng, Vincent Shing (Hong Kong University Press, 2019)
Although the official propaganda surrounding the drug detainees in China is that of helping, educating, and saving them from their drug habits and the drug dealers who lure them into drug abuse, it is clear, according to Vincent Shing Cheng, that those who have gone through the rehabilitation system lost their trust in the Communist Party's promise of help and consider it a failure. Based on first-hand information and established ideas in prison research, Hypocrisy gives an ethnographic account of reality and experiences of drug detainees in China and provides a glimpse into a population that.